Manipulation and Domestic Abuse in Contested Contact – Threats to Children's Participation Rights. (28th April 2020) - Morrison, Fiona; Tisdall, E. Kay M.; Callaghan, Jane E. M.
Abstract : The United Nations Convention on the Rights of the Child has catalysed numerous jurisdictions to introduce new legal provisions to support children's participation rights when child contact is contested. Despite this, children's participation is frequently limited in practice, especially in contexts where children are perceived as vulnerable to a parent's manipulation, even if there are allegations of domestic abuse. While "resist and refusal dynamics" have yet to become mainstream terms in Scottish family law, "manipulation" has become a common concern in cases of contested contact. Drawing on a Scottish empirical study on contested child contact in circumstances of domestic abuse, we interrogate the implications that the concept of manipulation has for children's participation rights. The study involved separate in‐depth interviews with 18 children and their 16 mothers. Findings point to concerns about upholding children's participation rights, particularly in cases where children were depicted as "influenced" or "manipulated." Through our analysis, we disentangle the problems professionals have when concerns about child manipulation and domestic abuse intersect. We argue that, when combined, allegations of manipulation and domestic abuse present a significant and serious risk to children's participation rights. We find the legal construction of the child's views as separate from the parental dispute to have unintended and serious consequences for children's participation rights. We offer ways in which law and practice may evolve to ensure children's participation rights in these contexts are both implemented and upheld. Practitioner's Key Points: The combination of allegations of manipulation and domestic abuse present a significant and serious risk to children's participation rights in contested child contact A legal construction of the child's views as separate to the parental dispute to have unintended and serious consequences for children's participation rights Radical reform in family law and practice is necessary to make disputes about child contact centered around the child, rather than on parental responsibilities and rights.